2012
DOI: 10.1121/1.4731224
|View full text |Cite
|
Sign up to set email alerts
|

Comparing behavioral and physiological measures of combination tones: Sex and race differences

Abstract: Both distortion-product otoacoustic emissions (DPOAEs) and performance in an auditory-masking task involving combination tones were measured in the same frequency region in the same ears. In the behavioral task, a signal of 3.6 kHz (duration 300 ms, rise/fall time 20 ms) was masked by a 3.0-kHz tone (62 dB SPL, continuously presented). These two frequencies can produce a combination tone at 2.4 kHz. When a narrowband noise (2.0-2.8 kHz, 17 dB spectrum level) was added as a second masker, detection of the 3.6-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 68 publications
3
14
0
Order By: Relevance
“…From the outset, the study was designed to measure sex differences in both the psychoacoustical tasks and the physiological measures, and, for the female subjects, also to measure any differences across the menstrual cycle. As noted above, after all the data were collected, we noticed some unanticipated race/ethnic effects (McFadden et al, 2012b), so that variable is included in the analyses here. Because racial background was not systematically considered during recruitment, all outcomes relevant to that variable must be viewed as highly tentative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the outset, the study was designed to measure sex differences in both the psychoacoustical tasks and the physiological measures, and, for the female subjects, also to measure any differences across the menstrual cycle. As noted above, after all the data were collected, we noticed some unanticipated race/ethnic effects (McFadden et al, 2012b), so that variable is included in the analyses here. Because racial background was not systematically considered during recruitment, all outcomes relevant to that variable must be viewed as highly tentative.…”
Section: Methodsmentioning
confidence: 99%
“…(Overshoot is the difference in detectability of a brief tonal signal when its onset occurs soon after the onset of a wideband masker versus later in its time course; two-tone suppression is the difference in forward masking for a brief tone masked only by another tone of the same frequency versus masked by that tone plus another tone slightly higher in frequency.) By contrast, males are reported to be better than females at frequency discrimination and loudness discrimination (Rammsayer and Troche, 2012), at sound localization (reviewed by McFadden, 1998;Z€ undorf et al, 2011), at using an off-frequency cue in a simultaneous tone-on-tone masking task (the Greenwood effect; see McFadden et al, 2012b), and at detecting a tonal signal in the presence of a wideband masker whose frequency content varies from presentation to presentation (called profile analysis; see Neff et al, 1996). It is not clear what factor(s) links these psychoacoustical tasks, but some of these previously studied tasks are among the seven studied for this report.…”
Section: Introductionmentioning
confidence: 99%
“…Our standard procedure when collecting DPOAE data (see McFadden et al, 2012) is to step a pair of equal-level primary tones over a range of frequencies (with the ratio of the primaries fixed at 1.21), obtain an input/output function at each of six frequency steps, and then create a composite input/output function using the median DPOAE level at each primary-tone level tested (as a way to reduce the effects of microstructure on our estimate of DPOAE strength over that range of primary frequencies). The composite function is fitted with a straight line over its linear range, and the primary level necessary to produce a DPOAE equal to −5 dB SPL is determined from the fitted line.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that women had more favorable hearing threshold than men, and their right ears hearing responses were better than those of the left ears ( McFadden, 2009 ; McFadden, Pasanen, Leshikar, Hsieh, & Maloney, 2012 ). The present study showed a higher level of hearing loss in men, as the level of hearing loss in the left ear was higher than that in the right ear, and in case of any limitation at cervical movements, the level of hearing loss in the left ear was higher than that in the right ear ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%